Bone marrow MSC from pediatric patients with B-ALL highly immunosuppress T-cell responses but do not compromise CD19-CAR T-cell activity - Samanta Romina Zanetti; Paola Alejandra Romecin; Meritxell Vinyoles; Manel Juan; José Luis Fuster; Mireia Cámos; Sergi Querol; Mario Delgado; Pablo Menendez (Journal for ImmunoTherapy of Cancer)
Background Although adoptive transfer of CD19-directed chimeric antigen receptor (CAR) T-cells (CD19-CAR T-cells) achieves high rates of complete response in patients with B-cell acute lymphoblastic leukemia (B-ALL), relapse is common. Bone marrow (BM) mesenchymal stem/stromal cells (BM-MSC) are key components of the hematopoietic niche and are implicated in B-ALL pathogenesis and therapy resistance. MSC exert an immunosuppressive effect on T-cells; however, their impact on CD19-CAR T-cell activity is understudied.Methods We performed a detailed characterization of BM-MSC from pediatric patients with B-ALL (B-ALL BM-MSC), evaluated their immunomodulatory properties and their impact on CD19-CAR T-cell activity in vitro using microscopy, qRT-PCR, ELISA, flow cytometry analysis and in vivo using a preclinical model of severe colitis and a B-ALL xenograft model.Results While B-ALL BM-MSC were less proliferative than those from age-matched healthy donors (HD), the morphology, immunophenotype, differentiation potential and chemoprotection was very similar. Likewise, both BM-MSC populations were equally immunosuppressive in vitro and anti-inflammatory in an in vivo model of severe colitis. Interestingly, BM-MSC failed to impair CD19-CAR T-cell cytotoxicity or cytokine production in vitro using B-ALL cell lines and primary B-ALL cells. Finally, the growth of NALM6 cells was controlled in vivo by CD19-CAR T-cells irrespective of the absence/presence of BM-MSC.Conclusions Collectively, our data demonstrate that pediatric B-ALL and HD BM-MSC equally immunosuppress T-cell responses but do not compromise CD19-CAR T-cell activity.